Asymmetry in socio-technical knowledge: A theoretical framework for the study of environmental conflicts - Parker, Cristián; Pérez Valdivia, José Miguel (Revista de Sociología, 2019)
The objective of the present article is to propose a theoretical and methodological framework for the analysis of socio-technical knowledge as a factor in environmental assessment processes. This is done in the context of the evaluation procedures typically employed as part of infrastructure, energy and mining megaprojects. In particular, we will explore a theoretical approach that addresses the social construction of socio-environmental and socio-technical knowledge, as well as the asymmetries of the social actors involved and the risk of the formation of a technocracy that inhibits participation. We propose a methodological framework for the study and analysis of the discursive and semiotic expressions of the discourses within which negotiated knowledge may be found during environmental assessment processes. The framework is proposed as a means of identifying and managing asymmetries in socio-technical knowledge. It is an issue which has been addressed by few studies to date, despite its relevance to the emergence, development and outcome of socio-environmental conflicts.